The moderators affect on the usage of mobile banking in Malaysia - Wong, Liana Jing Yi (2023)
Mobile banking is an online platform that provides the public with the opportunity to carry out daily banking and commercial transactions through a mobile application. In Malaysia, mobile banking users and transactions are increasing at a steady rate year by year. However, there are still some factors that hinder the public from adopting and using mobile banking applications. The factors are usually affected by the demographic background of the users. Due to this issue, the Unified Theory of Acceptance and Use of Technology (UTAUT) 2 model is useful in examining the factors influencing users’ technology acceptance. However, modification of the model is required to further examine how demographic backgrounds as moderators can affect the usage of mobile banking in Malaysia. Taking account of this context, the objective of this study is to determine the factors that affect the usage of mobile banking in Malaysia. In addition, this study also aims to determine the most significant factors that affect the usage of mobile banking in Malaysia. Not only that, but this study also aims to examine the moderator's effect between the factors and the usage of mobile banking in Malaysia. In this study, the UTAUT2 model has been modified by removing some variables and adding some moderators to alter the relationship between the dependent variable and the independent variable. From the perspective of methodology, secondary data will be utilised. The dataset was collected by the previous researchers using non-probability sampling, and the previous researchers have successfully collected responses from 504 respondents. The findings indicated that facilitating conditions, perceived risk, habit, and interface design quality will affect the usage of mobile banking in Malaysia. Among all these factors, the most significant factor is interface design quality, which affects the usage of mobile banking in Malaysia. The findings also revealed that the three moderators selected can moderate the relationship between facilitating condition, perceived risk, habit, interface design quality, and mobile banking usage.